1997
DOI: 10.1073/pnas.94.18.9679
|View full text |Cite
|
Sign up to set email alerts
|

p53-independent apoptosis induced by paclitaxel through an indirect mechanism

Abstract: The efficacy of chemotherapeutic agents may be determined by a number of different factors, including the genotype of the tumor cell. The p53 tumor suppressor gene frequently is mutated in human tumors, and this may contribute to chemotherapeutic resistance. We tested the requirement for wild-type p53 in the response of tumor cells to treatment with paclitaxel (trade name Taxol), an antineoplastic agent that stabilizes cellular microtubules. Although paclitaxel is broadly effective against human tumor xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 41 publications
5
93
0
1
Order By: Relevance
“…Results of this study demonstrated that paclitaxel in this range of concentrations activated IL-6 through the activation of JNK signaling pathway but not through the LPS-like activity of paclitaxel. First, the 1 mM concentration of paclitaxel used in this study was much lower than that reportedly (3-140 mM) effective for upregulation of IL1alpha, IL-1 beta, IL-8 and TNF-alpha (Ding et al, 1990;Lee et al, 1996;Lanni et al, 1997;Kawasaki et al, 2000Kawasaki et al, , 2003Perera et al, 2001;Takeda et al, 2003). Second, no upregulation of TLR4, MyD88, or NF-IL6 in terms of mRNA levels in BR cells treated with 1 mM paclitaxel was noted (Figure 6a).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Results of this study demonstrated that paclitaxel in this range of concentrations activated IL-6 through the activation of JNK signaling pathway but not through the LPS-like activity of paclitaxel. First, the 1 mM concentration of paclitaxel used in this study was much lower than that reportedly (3-140 mM) effective for upregulation of IL1alpha, IL-1 beta, IL-8 and TNF-alpha (Ding et al, 1990;Lee et al, 1996;Lanni et al, 1997;Kawasaki et al, 2000Kawasaki et al, , 2003Perera et al, 2001;Takeda et al, 2003). Second, no upregulation of TLR4, MyD88, or NF-IL6 in terms of mRNA levels in BR cells treated with 1 mM paclitaxel was noted (Figure 6a).…”
Section: Discussionmentioning
confidence: 60%
“…At high concentrations (5-30 mM), paclitaxel has been reported to exert endotoxin LPS-like effects through treatment on macrophage-like cells, including the upregulation of various cytokines (Ding et al, 1990;Lee et al, 1996;Lanni et al, 1997). Lipopolysaccharidelike effects of paclitaxel were thought to be conveyed through TNF receptor (Ding et al, 1990) or TLR-4 (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Despite its unlikely clinical relevance due to the suprapharmacologic concentration of paclitaxel required, this observation still strengthens the notion that paclitaxel has multiple effects on the cell. Paclitaxel is also shown to activate interleukin (IL)-8 transcriptionally in ovarian carcinoma cells, 90 and the transcription factor (AP-1, NF-B) binding sites of the IL-8 promoter are required for activation by paclitaxel.…”
Section: Paclitaxel May Activate the Release Of Cytotoxic Cytokinesmentioning
confidence: 73%
“…Also data concerning p53 alterations have been reported 47,48 but with contradictory conclusions explained as due to the differences in laboratory assays utilised and characteristics of clinical series considered.…”
Section: Discussionmentioning
confidence: 99%